Kelayakan Bahan Ajar Teks Negosiasi Berbasis Etnis Batak Simalungun Berbantuan Aplikasi untuk Meningkatkan Pembelajaran Kelas X SMK PAB 5 Klambir Lima - Rika Kartika; Heri Setiawan (Journal on Education, 2022)
This study aimed to describe the process of Appropriateness, validation, feasibility, and effectiveness of using Simalungun ethnic-based teaching materials with application-assisted applications on negotiating text materials for class X SMK. This study was conducted in SMK PAB 5 Klambir V. The research method is Research and Development (R&D) with a 4D model including Definition, Design, Development, and Dissemination with a population as 48 students. This study used a purposive sampling technique with a total of 23 students. The types of data include qualitative and quantitative data. The result of the study is a product of teaching materials in the form of a textbook based on Simalungun Batak ethnic. According to the results of the material expert validation, validator I as 75%, and validator II as 98%. While the results of validation by design experts are validator I as 96%, and validator II as 84%. These data indicated that the teaching materials are valid and feasible to be tested in schools. The materials were tested in SMK PAB 5 Klambir V with a class X TKJ-2 as the sample, the teacher's response was 92%. The data were obtained from questionnaires consisting of the results of a small group trial categorized as "Very Satisfactory", the results of a limited trial categorized as "Very Satisfactory" and the results of a wider trial with the category "Very Satisfactory." These data indicated that the teaching materials are valid and suitable to be used in schools. It can be concluded that the teaching materials based on the Simalungun Batak ethnic are suitable to be used in classroom learning.